Issues For Detection Of Fraud And Errors In Financial Statements - Shukurullaevich, Khajimuratov Nizomjon (International Journal of Psychosocial Rehabilitation, 2020)
This article describes irregularities and other cases of fraud in the preparation of financial statements. As a result of the research, areas with a high risk of misstatement of financial statements and areas for its elimination have been recommended.